An upscale theory of thermal-mechanical coupling particle simulation for non-isothermal problems in two-dimensional quasi-static system. Issue 7 (5th October 2015) - Xia, Ming
Abstract : Purpose: – The purpose of this paper is to present an upscale theory of the thermal-mechanical coupling particle simulation for non-isothermal problems in two-dimensional quasi-static system, under which a small length-scale particle model can exactly reproduce the same mechanical and thermal results with that of a large length-scale one. Design/methodology/approach: – The objective is achieved by extending the upscale theory of particle simulation for two-dimensional quasi-static problems from an isothermal system to a non-isothermal one. Findings: – Five similarity criteria, namely geometric, material (mechanical and thermal) properties, gravity acceleration, (mechanical and thermal) time steps, thermal initial and boundary conditions (Dirichlet/Neumann boundary conditions), under which a small-length-scale particle model can exactly reproduce both the mechanical and thermal behavior with that of a large length-scale model for non-isothermal problems in a two-dimensional quasi-static system are proposed. Furthermore, to test the proposed upscale theory, two typical examples subjected to different thermal boundary conditions are simulated using two particle models of different length scale. Originality/value: – The paper provides some important theoretical guidances to modeling thermal-mechanical coupled problems at both the engineering length scale (i.e. the meter scale) and the geological length scale (i.e. the kilometer scale) using the particle simulation method directly. The related simulation results from two typical examples of significantly different length scales (i.e. a meter scale and a kilometer scale) have demonstrated the usefulness and correctness of the proposed upscale theory for simulating non-isothermal problems in two-dimensional quasi-static system.